Kiła, ospa, angielskie poty. Zapomniane epidemie w Prusach i na Pomorzu w latach 1527 i 1529. - Możdżeń, Julia (Studia Historica Gedanensia, 2021)
This article aims to analyze narrative material recorded in Prussian and Pommeranian towns in the course of an epidemic of syphilis and smallpox in 1527 and of English sweats in 1529 (chroniclers' accounts and letters). The point of departure is the extensive and detailed description contained in the Preuβische Chronik by the Gdańsk chronicler Simon Grunau. To test its credibility, the information it contains is compared with other current accounts on the subject of the course of the epidemics. Hitherto the epidemics of 1527 and 1529 have not aroused the interest of scholars writing about Prussia and Pomerania. The author of this article has collected manuscripts and printed source material, which is included in an annex. The article analyzes: the reactions to the appearance of sickness on the part of city authorities noted by chroniclers (including, Simon Grunau, Thomas Kantzow, and Johannes von Freiberg) and of the inhabitants of Szczecin, Gdańsk, Königsberg, Toruń, and Elbląg; descriptions of the remedial measures proposed; and interpretations of the ways the sicknesses spread among people and domestic animals. The article compares these with accounts surviving in contemporary letters, including those of Martin Luther, Prussian Duke Albrecht Hohenzollern, and Philip Melanchthon; it also considers accounts from the extensive medical writing preserved in old printed texts. An analysis of the epidemic of 1527 makes it possible to identify several diseases (smallpox and bird flu) that chroniclers identify with syphilis. The surviving accounts of witnesses point to convergent reactions of people to new illnesses with those observed today.